Nutritional Status and Quality of Life among Hemodialysis Patients in Malaysia - Md. Yusop, Nor Baizura (2007)
Hemodialysis treatment provides progressive improvement in decreasing the risk of mortality and mobility. However, insufficient hemodialysis treatment and hemodialysis related complications tend to decrease patient’s nutritional status and overall quality of life. The objective of this cross-sectional study was to determine the nutritional status and quality of life among hemodialysis patients. A total of 90 subjects were recruited from Hospital Kuala Lumpur and dialysis centres of the National Kidney Foundation of Malaysia. Data on socioeconomics, demography, medical history, hemodialysis treatment and nutritional status were collected. Anthropometry assessment included weight, height, mid-arm circumference and mid-arm muscle circumference, skin fold thicknesses at four sides (biceps, triceps, subscapular and suprailliac), calf circumference and bioimpedance assessment. Subjective Global Assessment was conducted. Biochemical indices including renal function test, liver function test, glucose test, electrolytes, lipid profile, hemoglobin and hematocrit were ascertained. Information on dietary intake were collected using 24-hour diet recall and one-day food record. Information on appetite level and eating habits were collected. Kidney Disease Quality of Life Short Form was used to determine quality of life of the subjects. Subjects comprised 48.9% males and 51.1% females. The sample size predominately Chinese (n=62, 68.9%), followed by Malays (n=19, 21.1%), Indians (n=7, 7.8%) and others (n=2, 22.0%). The mean age of subjects was 49.7 ± 14.1. Approximately 30% of the subjects achieved the recommended body mass index for hemodialysis patients. Approximately 80% and 34% of the subjects had triceps skinfold and mid-arm circumference less than 50th percentiles, respectively. Approximately 48% subjects had serum albumin level lower than 4.0 mg/dL. About 58.6% had elevated serum phosphate (> 1.6 mmol/L). For lipid profile, 28.8% subjects had elevated total cholesterol (> 5.2 mmol/L), 71.1% had serum cholesterol of less than 5.2 mmol/L. The mean total energy and protein intake was 26.8 ± 7.0 kcal/kg and 1.0 ± 0.3 g/kg, respectively. Results of the Kidney Disease Quality of Life Short Form analysis showed that the highest score was for dialysis staff encouragement (75.28 ± 23.55). The lowest score was for work status (27.78 ± 34.4). In the General Linear Model univariate analysis, blood flow was found to contribute to complication of the kidney, while calf circumference and mid-arm muscle circumference were predictors for the support and satisfaction of the treatment, blood flow, serum albumin, serum creatinine and protein intake were predictors for the physical health composite. As for mental health composite, diabetes was the only contributory factor. Multivariate regression showed similar results were obtained with exception of treatment support and satisfaction. In conclusion, low blood flow, diabetes, increased serum calcium and low serum creatinine had an impact on quality of life of the subjects. Longitudinal study is required to determine the cause and effect mechanism between the associated factors and quality of life.